Amorphous fraction controlled mechanical and optical properties of polylactic acid below glass transition temperature. (November 2020) - Yu, Tsung-Han; Su, Yu-Hsun; Huang, Hsuan-Hao; Tsai, Hsin-Jung; Hsu, Wen-Kuang
Abstract: A negative relation between strength and crystallinity is observed in polylactic acid below glass transition temperature. Study indicates that entangled molecules in amorphous regions act as load bearing structures and are responsible for stress induced crazing. A three-phase model is proposed to explain how amorphous fraction changes with heat treatments and contributes to polymer modulus below glass transition temperature. Incorporation of carbon quantum dots into amorphous fraction dominated PLA creates a new type of luminescent composites that can be used for food labelling, tracking, packaging and production of origin. Graphical abstract: A contrary relationship is realized between strength and crystallinity of PLA below glass transition temperature. Image 1 Highlights: A contrary relationship is realized between strength and crystallinity of polylactic acid (PLA) below glass transition temperature. Entangled molecules in amorphous regions act as load bearing structures and are responsible for stress-induced crazing. Incorporation of carbon quantum dots into amorphous PLA creates a new type of luminescent composites that show a great potential in tracking, coding and packaging for production of origin.